The Role of Cardiac Imaging in Heart Failure with Reduced Ejection Fraction - Rebecca C Gosling; Abdallah Al-Mohammad (Cardiac Failure Review)
Heart failure (HF) is a major health burden associated with significant morbidity and mortality. Approximately half of all HF patients have reduced ejection fraction (left ventricular ejection fraction <40%) at rest (HF with reduced ejection fraction). The aetiology of HF is complex, and encompasses a wide range of cardiac conditions, hereditary defects and systemic diseases. Early identification of aetiology is important to allow personalised treatment and prognostication. Cardiac imaging has a major role in the assessment of patients with HF with reduced ejection fraction, and typically incorporates multiple imaging modalities, each with unique but complimentary roles. In this review, the comprehensive role of cardiac imaging in the diagnosis, assessment of aetiology, treatment planning and prognostication of HF with reduced ejection fraction is discussed.